Anemia is associated with dietary and sleep quality in Indonesian adolescent girls: A cross-sectional study - Lita Fitria; Ikha Deviyanti Puspita (Al-Sihah : The Public Health Science Journal, 2020)
Adolescent girls are one of the vulnerable age groups who are anemia. Many factors can affect Anemia on young girls such as dietary knowledge, weight loss dietary behavior, and sleep quality. Dietary knowledge can affect dietary behavior. The purpose of the study was to find out the correlation between dietary knowledge, weight loss dietary behavior, and sleep quality with anemia symptoms in SMA Negeri 14 Bekasi, Indonesia. This study method used quantitative observational by cross-sectional approach with random sampling design. 64 adolescent girls aged 15-18 years of 14 high school Bekasi were included as study participants. The study was conducted on 23 April 2020. Measurement of data using the questionnaire. The data were analyzed by the Pearson test with α=0.05. The result of the study showed that there was no correlation between dietary knowledge with anemia symptoms (p=0.686). No correlation between weight loss dietary behavior with anemia symptom (p=0.773). And there is a correlation between sleep quality with anemia symptom (p=0.049). It is recommended to increase knowledge and understanding about diet and dietary behavior, sleep quality, and symptoms of anemia can improve dietary behavior and better sleep quality, as well as, giving blood-supplemented tablets and consuming it regularly as an effort to reduce anemia on an adolescent girl.